Hubungan Personal Hygiene Dengan Keberadaan Escherichia Coli Pada Makanan Di Tempat Pengolahan Makanan (Tpm) Buffer AreaBandara Adi Soemarmo Surakarta - Romanda, Fitka (2016)
ABSTRACT Fitka Romanda, J500120020, 2012, RELATIONS OF PERSONAL HYGIENE WITH THE PRESENCE OF Escherichia coli IN FOOD PROCESSING (TPM) BUFFER AREA ADI SOEMARMO AIRPORTS SURAKARTA Fitka Romanda¹, Priyambodo², Erika Diana Risanti2 Faculty of Medicine, University of Muhammadiyah Surakarta Background. The existence of Escherichia coli in water or food is a sure indication of human fecal contamination by Escherichia coli which can have an impact on Extraordinary Events food poisoning in developing countries, especially in Indonesia. Escherichia coli contamination in food can be caused by other worst personal hygiene factor of food handlers. Aim. Knowing the relation of personal hygiene's food handlers relationship Escherichia coli. Method. This study was an observational study with cross sectional approach. 65 observations on food handlers and taking 65 samples of food at 22 Place Food Processing Buffer Area Adi Soemarmo Airports Surakarta. Results. The results showed the existence of a personal relationship with the presence of Escherichia coli hygiene in food at the Food Processing Buffer Area Sites Adi Soemarmo Surakarta with the statistical test used is Chi Square test and got p value (0.000) and the strength of relationship is with the C (0.477) Conclusion. Based on the results of the study, concluded there is a relationship of personal hygiene of food handlers to the presence of Escherichia coli in foods in the food processing (TPM) buffer area Adi Soemarmo Surakarta. Keywords. Personal Hygiene, Escherichia coli, Buffer Area 1The Student of Medical Faculty, Muhammadiyah Surakarta University 2The Lecturer of Medical Faculty, Muhammadiyah Surakarta University